Antibiofilm Effect of Sequential Application of Ozonated Water, Acetic Acid and Lactic Acid on Salmonella Typhimurium and Staphylococcus aureus Biofilms In Vitro - Parvin Mahdavi; Javad Aliakbarlu (Journal of Food Protection, 2024)
Biofilms are highly resistant to disinfectants and antimicrobials and are known as the primary source of food contamination. Salmonella Typhimurium (S. Typhimurium) and Staphylococcus aureus (S. aureus) have an excellent ability to form biofilm. This study aimed to evaluate the antibiofilm activity of ozonated water (O), acetic acid (AA), and lactic acid (LA), individually and sequentially, against biofilms of S. Typhimurium and S. aureus formed on the polystyrene surfaces. The antibiofilm effects of the treatments were evaluated using crystal violet staining and the viable count determination methods. In the staining method, the highest percentage of biofilm mass reduction was induced by successive use of ozonated water and acetic acid (O-AA), which reduced S. aureus biofilm mass by 44.36%. The sequential use of ozonated water and lactic acid (O-LA) could decrease S. Typhimurium biofilm mass by 57.26%. According to the viable count method, the most effective treatment was the sequential use of ozonated water and lactic acid (O-LA), which reduced S. aureus and S. Typhimurium biofilms by 1.76 and 4.06 log, respectively. It was concluded that the sequential use of ozonated water and organic acids can be considered a practical and environmentally friendly approach to control biofilms.